Impact of β‐blocker therapy on right ventricular function in heart failure patients with reduced ejection fraction. A prospective evaluation. Issue 9 (20th August 2020) - Galves, Rémi; Da Costa, Antoine; Pierrard, Romain; Bayard, Geoffrey; Guichard, Jean Baptiste; Isaaz, Karl
Abstract: Background: Beta‐blocker (β‐blocker) therapy has been shown to improve mortality and reduce hospitalizations in patients with heart failure (HF) with reduced ejection fraction (HFrEF). Although the physiological action mechanisms of β‐blockers are well described, their effects on right ventricular (RV) function have not been prospectively studied. Objective: This prospective study aimed to (a) evaluate whether β‐blocker therapy impacts RV remodeling based on echo parameters and (b) determine the predictive echo factors of β‐blocker therapy response. Methods: From September 2017 to September 2018, HF patients were prospectively enrolled using CIBIS criteria: Class II, III, or IV HF; left ventricular ejection fraction (LVEF) of ≤40%; hospitalized for HF within the previous 12 months. Echo evaluation was performed before initiating β‐blocker therapy and 3 months after optimal dose adjustment. Based on previous studies, patients with (absolute) LVEF ≥ 5% improvement were considered significant β‐blocker therapy responders. Results: Overall, 40 patients (pts) completed the study, characterized as follows by age: 70 ± 10 years; gender: 10 women; cardiomyopathy etiology: idiopathic in 24 and ischemic in 16; NYHA Class: II in 22 and III in 10; LVEF: 32 ± 5%; and NTProBNP: 2665 ± 2400 pg/mL. The final population comprised 32 pts (79%), with eight (21%) excluded: two because of β‐blocker therapy intolerance, one lost to follow‐up, and five withdrew from the study. Under β‐blocker therapy, several echo parameters significantly improved: LVEF from 31.7 ± 9 to 40.5 ± 9 ( P  < .0001); LV end‐diastolic volume (EDV) from 154 ± 54 to 143 ± 45 mL ( P  = .06); LV end‐systolic volume (ESV) from 107 ± 49 to 88 ± 37 mL ( P  = .0006); LV ES from 46 ± 11 to 64 ± 13 mL ( P  = .008); LV end‐diastolic diameter (EDD) from 57 ± 9 to 54 ± 6 mm ( P  = .04); LV end‐systolic diameter (ESD) from 48 ± 10 to 44 ± 7 mm ( P  = .007); and right ventricular systolic pressure (RV SP) from 39 ± 10 to 32 ± 8 mm Hg ( P  = .0001). Significant modifications were observed in terms of RV echo parameters: right ventricular (RV) size decreased from 30 ± 4 to 27 ± 5 mm ( P  = .03), while RV systolic function significantly improved based on tricuspid annular plane systolic excursion (TAPSE) (16.5 ± 4 vs. 19 ± 4 mm; 0.0006); DTI‐derived tricuspid lateral annular systolic velocity wave (S′) ( 10 ± 2 vs. 11.3 ± 3 cm/s; P  = .03); and RIMP (Tei index) (0.5 ± 0.1 vs 0.46 ± 0.1; P  = .04). RV 2D fractional area change (%) did not significantly differ despite a clear improvement tendency (35 ± 6 vs. 37 ± 4%; P  = .1). No significant modifications were observed concerning LV diastolic parameters. Overall, β‐blocker echo responders (n = 23/32; 72%) exhibited the same left and right echo parameters. No echo variables predicted the β‐blocker response. Conclusions: In HFrEF pts, β‐blocker therapy significantly improves LV and RV systolic remodeling. Accordingly, β‐blocker therapy could be applied as soon as possible in HFrEF patients with right ventricular dysfunction so as to limit RV remodeling.